2022
DOI: 10.1111/eufm.12386
|View full text |Cite
|
Sign up to set email alerts
|

Russia–Ukraine crisis: The effects on the European stock market

Abstract: We examine the effect of the Russia–Ukraine crisis on the European stock markets. Because of increased political uncertainty, geographic proximity and the ramifications of the fresh sanctions imposed on Russia, the European stock markets tended to react negatively to this crisis. We find that on 21 February 2022, when Russia recognized two Ukrainian states as autonomous regions, European stocks incurred a significant negative abnormal return. Moreover, the negative stock price reactions continued in the post‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…Our study confirms and expands the conclusion made by Ahmed et al (2022) in a broader industrylevel perspective that, in general, investors in the three countries have taken the Russia-Ukraine crisis seriously enough. The war's adverse impact has already spread from political field to panics about energy supply, financial stability, and long-term economic development.…”
Section: Conclusion Remarks and Future Research Agendasupporting
confidence: 88%
See 3 more Smart Citations
“…Our study confirms and expands the conclusion made by Ahmed et al (2022) in a broader industrylevel perspective that, in general, investors in the three countries have taken the Russia-Ukraine crisis seriously enough. The war's adverse impact has already spread from political field to panics about energy supply, financial stability, and long-term economic development.…”
Section: Conclusion Remarks and Future Research Agendasupporting
confidence: 88%
“…Moreover, sanctions imposed as a result of the crisis could impair financial intermediation and trade, raising fears of slower economic growth and faster inflation around the world. Thus, the impact of this crisis is much broader and more profound than that of previous political events, as proposed by Ahmed et al, 2022. Salisu et al (2022 also demonstrated that geopolitical threats such as military build-ups have a greater negative impact on stock returns than the actual occurrence of geopolitical behavior, while more specific research on industries is expected to be conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a huge negative impact on CAR for countries with close boundaries with EU countries. (Ahmed et al, 2022) analysed that the crisis of the Russia-Ukraine war led to a negative stock return for European stocks even after the event period.…”
Section: Literature Reviewmentioning
confidence: 99%